Transformasi Pembelajaran Pendidikan Agama Kristen di Era Digital - Mega Nurhayani Saragih; Juni Wando Purba (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2025)
This article aims to: 1) analyze the transformation of Christian Religious Education learning in the digital era. 2) analyze the integration of deep learning approaches and artificial intelligence in Christian Religious Education learning. 3) analyze the integration of artificial intelligence in stimulating the development of Christian faith and spirituality of participants. 4) develop a model for the transformation of Christian Religious Education learning in the digital era. The article was written using a literature study method through an in-depth review of various scientific articles published in reputable international journals, national journals indexed at least SINTA 2, books, and relevant scientific documents. Based on the results of the analysis, it was found that technological developments encourage the transformation of Christian Religious Education learning that emphasizes a learner-oriented approach, through collaborative, participatory, interactive, and contextual learning activities. The use of digital platforms, artificial intelligence, and the application of deep learning. However, the transformation of Christian Religious Education learning in the digital era finds challenges for institutions, educators, and students, specifically related to ethical and theological issues related to healthy social relations as part of stimulating the development of students' faith and spirituality. Thus, the use of technology in Christian Religious Education learning needs to be based on the values of Christian faith and spirituality as a whole.